METODE PEMBERDAYAAN ANGGOTA GERAKAN PEMUDA ANSOR ANAK CABANG PUCAKWANGI MELALUI SEKOLAH PEMBERDAYAAN DESA - Nurwiyanti, Ike (Community Development: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to determine the method of empowering members of the Youth Movement (GP) Ansor Youth Leaders Pucakwangi Branch through village empowerment schools as well as the driving factors and inhibiting factors in empowering the Youth Movement Members (GP) Ansor Youth Leadership Branch (PAC) Pucakwangi through village empowerment schools ( case study of Pucakwangi Branch Sub-branch) in 2021. The type of research used by the researcher is field research, where the researcher seeks information directly by going to the Pucakwangi Branch Office (PAC). This study uses a qualitative approach. The data collection technique used by the researcher is to use observation, interviews and documentation. While the data analysis used by the researcher is descriptive analysis with the steps of collecting data, reducing data, presenting data, and drawing conclusions. The results of the research obtained by researchers when conducting research are (1) methods of empowering members of the Pucakwangi branch of Ansor Youth Movement members through village empowerment schools, namely participatory training methods, and the results of using participatory training methods are podcats, village empowerment schools (2) The driving factors and inhibiting factors in implementing the empowerment of members of the Pucakwangi Branch Youth Ansor Youth Movement through village empowerment schools. The driving factors are the high level of education of the management, the majority of the PAC board are former activists, the readiness of members of the Ansor Youth Movement to enter the community in empowering human resources and high ability to empower. the inhibiting factors are the lack of self-awareness of members to participate in empowerment activities, economic limitations, the low level of education of members of the Ansor Youth Movement, and the long distance that members of the Ansor Youth Movement have to travel to the PAC office.